Model Denda Berdasarkan Tingkat Inflasi untuk Mendukung Anggaran Belanja Negara yang Berkelanjutan - Benny Budiawan Tjandrasa; Ida Ida; Kayla Abigail Christy (Research Center and Case Clearing House PPM School of Management, 2022)
The imposition of fines in articles of the Criminal Code aims to provide a deterrent effect and as income for the state to compensate for the losses incurred, but some of the fines in the existing articles are so small that they do not cause a deterrent effect and do not provide significant income for the state. The inflation rate in Indonesia for several decades has made the determination of the value of fines in rupiah values in the prevailing articles no longer relevant for the sustainability of a deterrent effect and compensation for the state. This study proposes a model of fines that can be used sustainably with a value equivalent to the increase in inflation using multivariate regression analysis. The samples used are the prices of gold, silver, and platinum to represent precious metals, and the exchange rates used are USD and JPY. The test results of USD and platinum precious metal have a significant and positive correlation. Considering that the Republic of Indonesia is a sovereign country and does not want to depend on other countries' monetary systems or economic policies, it is advisable to choose the price of the platinum precious metal as the amount of the fine imposed in legal cases.